2022
DOI: 10.3389/fphar.2022.1017690
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial treatments of tamoxifen and SM6Met, an extract from Cyclopia subternata Vogel, are superior to either treatment alone in MCF-7 cells

Abstract: Synergistic drug combinations are not only popular in antibiotic, anti-microbial, immune disease (i.e., AIDS) and viral infection studies, but has also gained traction in the field of cancer research as a multi-targeted approach. It has the potential to lower the doses needed of standard of care (SOC) therapeutic agents, whilst maintaining an effective therapeutic level. Lower dosages could ameliorate the fundamental problems such as drug resistance and metastasis associated with current SOC therapies. In the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Previous studies have found that TAM therapy inhibits migration in MCF-7 cells but not in the resistant TAMR-1 cells [ 78 ]. Furthermore, it was reported that combination treatment leads to a more significant delay in cancer cell migration when compared with TAM monotherapy [ 79 , 80 ]. DEX monotherapy and combination with other anticancer agents such as doxorubicin and docetaxel results in a significant inhibitory effect on BC cell migration [ 81–83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that TAM therapy inhibits migration in MCF-7 cells but not in the resistant TAMR-1 cells [ 78 ]. Furthermore, it was reported that combination treatment leads to a more significant delay in cancer cell migration when compared with TAM monotherapy [ 79 , 80 ]. DEX monotherapy and combination with other anticancer agents such as doxorubicin and docetaxel results in a significant inhibitory effect on BC cell migration [ 81–83 ].…”
Section: Discussionmentioning
confidence: 99%
“…longifolia , and C. maculata, demonstrate anti-diabetic ( Chellan et al, 2014 ; Schulze et al, 2016 ), anti-obesity ( Pheiffer et al, 2013 ; Jack et al, 2018 ), and immune-stimulatory activities ( Murakami et al, 2018 ) and osteoclast formation inhibition ( Visagie et al, 2015 ); in addition to their useful application in nutraceutical, and cosmetic products ( Joubert et al, 2019 ). Particularly of relevance to the current study, the C. subternata Vogel extract, SM6Met, was shown in several studies to possess phytoestrogenic activity, to display ERα antagonism and ERβ agonism, to antagonize estrogen-induced proliferation in ER + BC cells ( Mfenyana et al, 2008 ; Louw et al, 2013 ; Visser et al, 2013 ; Mortimer et al, 2015 ; van Dyk, 2018 ) and to ameliorate BC in rats ( Visser et al, 2016 ; Oyenihi et al, 2018 ). Like SM6Met, the cup of tea (CoT) extract from C. subternata Vogel and the C. genistoides extract, P104, also exhibit phytoestrogenic properties and antagonize estrogen-induced proliferation in ER + BC cells ( Verhoog et al, 2007b ; Visser et al, 2013 ; Roza et al, 2017 ).…”
Section: Introductionmentioning
confidence: 92%